Immobilization of the SARS-CoV-2-receptor binding domain onto methacrylate-based monoliths for nano LC at 30 nL min−1 and application for research of its ligands. Issue 2 (20th December 2021) - Guillaume, Yves Claude; André, Claire
Abstract : For the design of novel potent molecules against therapeutic protein targets produced in a low quantity or that are very expensive, the development of miniaturized analytical techniques is of crucial importance. Abstract : For the design of novel potent molecules against therapeutic protein targets produced in a low quantity or that are very expensive, the development of miniaturized analytical techniques is of crucial importance. One challenging target is the receptor binding domain (RBD) of the SARS-CoV-2-spike protein (S), which mediates the binding of the virus to host cells. In the present study, the RBD protein was thus immobilized on polymethacrylate monoliths prepared in a miniaturized capillary column (25 μm internal diameter; 70 mm length) by in situ polymerization, which could offer low backpressure in Nano LC at 30 nL min −1 . The immobilized quantity of the expensive RBD protein on the organic monolith was very low, in the submicrogram range, i.e., 0.060 μg. The immobilization method reduced non-selective interactions between the ligand and the organic monolith matrix and maintained the functionality of RBD due to the high activity rate (96%). The performance of this miniaturized affinity capillary column was demonstrated for the rapid evaluation of a recognition assay induced by 1, 2, 3, 4, 6-pentagalloyl glucose (PGG), a known ligand of RBD, and by five other molecules. In addition, it was demonstrated that competitive experiments could be performed with our miniaturized system to reveal the existence of only one type of binding site for three ligands of RBD, namely carbenoxolone, simeprevir and irinotecan. All these results showed the potential of our analytical miniaturized affinity system for the determination of interactions between potential ligands and immobilized RBD of SARS-CoV-2 to aid in the battle against COVID-19.